Postoperative COVID-19 Pneumonia following Resection of a Large Thoracic Chondrosarcoma - Austin C. Kaidi; Michael B. Held; Paul J. Park; Wakenda K. Tyler (Case Reports in Orthopedics)
Case. A 57-year-old man presenting with two months of insidious shoulder pain was found to have a large thoracic chondrosarcoma invading the spinal canal. The patient’s orthopedic oncologist organized an interdisciplinary team including interventional radiology, thoracic surgery, neurosurgery, and plastic surgery. This allowed safe, en bloc tumor resection. The patient’s postoperative course was complicated by COVID-19 pneumonia, which was rapidly identified and medically managed with full recovery. Conclusion. Postoperative COVID-19 pneumonia can present insidiously and mimic other postoperative complications. Early identification and testing can promote rapid isolation, proper personal protective equipment use, and guide outcome-improving treatments.